Food Losses and Food Waste Versus Circular Economy - Maria Parlińska; Abhishek Pagare (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article aims to introduce the issue of food waste and all attempts to prevent action. Business and politics are almost interdependent, and any discussion of an economic nature is not complete without a political contribution. The role of politics and politicians in shaping economic activities was and is widely discussed. In the article, there will be a discussion on the problems of food losses and waste in Poland as the member of EU and in India. The idea of the topic came during the tenure of collaboration between representatives of both departments. Conclusions of the study found some similarities and a lot of differences between the countries. Studies have shown that negative attitude of house-hold towards food waste is not frequently reflected in consumers’ behavior, despite their fundamental knowledge on how to reduce food waste. Properly selected and presented information will stimulate both consumer’s attitude and behavior.